LA LUCHA POR LAS REFORMAS POLÍTICAS DESDE EL INDIGENISMO PUNEÑO. PRINCIPALES DEFENSORES DEL DERECHO INDÍGENA - GALVEZ CONDORI, WALTER SALVADOR (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
The peasants' struggle to defend their dignity, achieve their freedom and shield their fundamental rights was arduous from the beginning; contradictorily, the marginalization suffered by the Spaniards in the colonial era was minor compared to the bloody exploitation of which they were victims in the republican era, a time where the flags of freedom and autonomy of the country were raised utopianly -ideally for the one who even came in a noble gesture to offer their lives, always first in the battle line of the liberation struggle-. In this context, a generation of Puno intellectuals arose, many of them knowledgeable in law, who from different fronts contributed to the feat of recognition of the rights that the man from the countryside always deserved for his own condition as a human being. This article focuses on the stage from 1821 to 1920, considering the political, legal and constitutional context; as well as in the indigenista movement both in its political, cultural and social sphere, given that its relevance is not exhausted in the temporal or historical aspect, especially if it continues to be part of the reflection on identity as a social group and of general shape as a nation and as a country